RANCANG BANGUN APLIKASI DAN GATEWAY WIRELESS SENSOR NETWORK UNTUK PEMANTAUAN LAHAN TANAMAN JARAK - Nofianto, Rendi Haris; Jusak, Jusak; Susanto, Pauladie (Journal of Control and Network Systems, 2014)
One of highly prospective vegetable oil that can be used as raw material for biodiesel is Jatropha (Jathropa Curcas L.). But, in order to get the maximum oil quality, continuously controlled temperature and soil humidity are needed. consequently, plantation monitoring device is needed. Wireless Sensor network (WSN) Technology is used in this final project. WSN is a wireless network consisting of multiple sensors that work together to monitor physical and environmental conditions. Thus, this supporting device can facilitate monitoring temperature and soil humidity surrounding Jatropha plantation. WSN communication protocol testing , indicating that the reception of data according to the address of the destination node and a range of up to 100 meters . Viewer program outcomes and indicator readings each node can work properly in accordance with the instructions on the program visual basic 6.0